From Global Insights to National Impact: Advancing Cardio-Oncology in Iraq - Ajlan, Mustafa H.; Farhan, Hasan A.; Dakhil , Zainab A. (Journal of the Faculty of Medicine Baghdad, 2024)
Cancer remains a leading cause of mortality and morbidity worldwide. Advances in cancer therapies—including immunotherapies (e.g., checkpoint inhibitors, gene-targeted therapies), antibody-based cancer toxins, chemotherapy, radiotherapy, and surgery—have significantly improved survival rates 1,2. However, this progress has led to a surge in the prevalence of cardiovascular disease (CVD) among cancer survivors, now recognised as a leading cause of mortality in this population 3,4. These intersecting burdens highlight the growing need to prevent, detect, and manage cardiovascular complications in cancer care pathways and call for important initiatives in establishing cardio-oncology services globally.